KEBIJAKAN NASIONAL KEBAHASAAN DAN PELINDUNGAN BAHASA DAERAH - Khaerudin Kurniawan (Universitas Negeri Medan, 2017)
Abstract : National Linguistic and Regional Language Protection Policy. This study aims to discuss government policy in protecting regional languages and literature, including what has been done and what has been outlined in legislation. The subject of language policy in Indonesia includes: national language policy, foreign language policy, and local language policy. As a language of unity, the Indonesian language serves as: (1) the symbol of national pride, (2) the symbol of national identity, (3) a tool that allows the unification of various ethnic groups with their socio-cultural background and language into the national unity of Indonesia, and (4) interconnection and intercultural means of communication. As the language of the country, the Indonesian language functions as: (1) the official language of the state, (2) the language of instruction in education, (3) the means of communication at the national level for the purposes of planning and implementation of national development as well as the interests of government; Culture, science, and technology. Keywords: National Policy, Language Abstrak : Kebijakan Nasional Kebahasaan dan Pelindungan Bahasa Daerah. Bertujuan untuk membahas kebijakan pemerintah dalam melindungi bahasa dan sastra daerah, termasuk apa yang sudah dilakukan dan apa yang telah digariskan dalam peraturan perundang-undangan. Ihwal kebijakan kebahasaan di Indonesia meliputi: kebijakan bahasa nasional, kebijakan bahasa asing, dan kebijakan bahasa daerah. Sebagai bahasa persatuan, bahasa Indonesia berfungsi sebagai: (1) lambang kebanggaan nasional, (2) lambang identitas nasional, (3) alat yang memungkinkan penyatuan berbagai suku bangsa dengan latar belakang sosial budaya dan bahasanya masing-masing ke dalam kesatuan kebangsaan Indonesia, dan (4) alat perhubungan antardaerah dan antarbudaya. Sebagai bahasa negara, bahasa Indonesia berfungsi sebagai: (1) bahasa resmi kenegaraan, (2) bahasa pengantar di dalam pendidikan, (3) alat perhubungan pada tingkat nasional untuk kepentingan perencanaan dan pelaksanaan pembangunan nasional serta kepentingan pemerintahan, dan (4) alat pembangunan kebudayaan, ilmu pengetahuan, dan teknologi. Kata Kunci: Kebijakan Nasional, Kebahasaan